Technical Note: Arthroscopic Resection of Snapping, Interponating Annular Ligament of the Elbow - Thiele, Kathi; Akgün, Doruk; Al-Mutaresh, Faisal; Stöckle, Ulrich; Lacheta, Lucca; Moroder, Philipp (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
The indication for surgical treatment of lateral snapping elbow syndrome is recurrent joint blockage in combination with pain of the affected elbow joint. Different parts of the lateral synovial capsule sleeve complex, including the annular ligament itself, a hypertrophic synovial fold, or meniscus-like soft tissue interposition can lead to painful entrapment. Surgical treatment options can include an arthroscopic or open procedure. The aim of this technical note is to provide a step-by-step illustration of the authorsʼ preferred arthroscopic approach with a comprehensive review of literature on clinical outcome.
Keywords: snapping annulare ligament; PRUJ; joint blockage; lateral elbow pain